Moneycracy - Alessandro Fedele; Pierpaolo Giannoccolo (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
How do wage and other financial benefits affect the set of candidates for political office? In this theoretical paper, we answer the question by studying self-selection into politics of individuals with heterogeneous skills and heterogeneous motivations. Our predictions are in line with the efficiency wage results proposed by the extant literature when a benchmark model with skills as the sole relevant characteristic of individuals is considered. Welfare is increasing in the politicians'wage since the best, i.e., high-skilled, individuals are attracted to politics only if their remuneration covers their high opportunity costs. Our findings are remarkably different when motivation is also taken into account. Welfare is not likely to be maximized when the politicians'wage is relatively high, for high-skilled individuals with market-oriented rather than public-spirited motivation are attracted. Finally, we provide an overview of the labor market of politicians in Europe and suggest that the Italian Parliament might be representative of our inefficiency wage mechanism, which we call moneycracy.
Keywords: P16; J45; J24; J32; 330